Effect of Low Cobalt Loading on TiO2 Nanotube Arrays for Water-Splitting. (10th November 2014) - Pozio, Alfonso
Abstract : This work is intended to define a new possible methodology for the TiO2 doping through the use of an electrochemical deposition of cobalt directly on the titanium nanotubes obtained by a previous galvanostatic anodization treatment in an ethylene glycol solution. This method does not seem to cause any influence on the nanotube structure, showing final products with news and interesting features with respect to the unmodified sample. Together with an unmodified photoconversion efficiency under UV light, the cobalt doped specimen reports an increase of the electrocatalytic efficiency for the oxygen evolution reaction ( OER ).